A Hybrid Technique for Smart Parking Management System in a Smart City - Paban Panda, Patita; Sekhar Das, Sudhansu (International Journal of Engineering and Technology, 2018)
Considering the urban environment, we proposed a new model â€œParking Management Systemâ€. The complete model provides you the basic features of the parking system. The system designates an exact parking slot for the driver. On the basis of user requirement, it includes the proximity to destination and the cost of parking. The capacity of overall parking is utilized efficiently. The system approach solves the problem at individual decisions in a time driven sequence. This is the most favorable solution based on the allocation on present state affair and subject to the arbitrary incidents such as the request of the new user and availability of the parking space. At the next decision point, the allocation is updated ensuring that there is no conflicts in the resource reservation and the assignment of resource have the higher cost than the current cost of function value. The proposed system enables users to find out the free parking space on the cost on new performance metrics to calculate the cost of user parking under the consideration of distance and the total no of free places. The system show that the algorithm helps improves the probability of successful parking and the user waiting time is minimized. The proposed system is implemented by us in the real world successfully.Â Â